Kajian Pengawasan Unit Apron Movement Control terhadap Pemenuhan Standar Operasional Prosedur pada Area Apron di Bandar Udara Kalimarau Berau - Setiawan, Dodi; Sundoro; Dwi Lestary (Jurnal Ground Handling, 2025)
This research evaluates how effectively the Apron Movement Control (AMC) Unit oversees adherence to Standard Operating Procedures (SOP) regarding ground handling operations and the use of Ground Support Equipment (GSE) at Kalimarau Airport. The study stems from frequent violations occurring in the apron area, which pose potential threats to aviation safety, with the goal of strengthening safety culture in airside operations. Using a qualitative method, data were obtained through field observations, comprehensive interviews, and document analysis. The study focused on identifying recurring violations and assessing the current supervision system, with PR 21 Year 2023 serving as the primary guideline. Findings reveal that AMC's oversight is still lacking, as shown by common breaches such as GSE operating over speed limits, parking equipment outside designated zones, unauthorized aircraft run-up activities, and failure to wear personal protective equipment (PPE). To overcome these problems, the study proposes improved surveillance using CCTV and GPS tracking, ongoing personnel training, and the implementation of a structured reward and sanction system to promote SOP adherence within the apron environment.